KEBIJAKAN KRIMINALISASI TERHADAP PENANGKAPAN IKAN TERUBUK DALAM PERATURAN DAERAH KABUPATEN BENGKALIS - Widya Lestari; Erdianto Erdianto; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The decision of the Minister and the Regent regarding the status of protection of terubuk fish does not create a deterrent effect for the perpetrators of the violation, because even though they are given a warning letter and make a statement not to repeat their actions, there are still many violations committed by other offenders even though they already know the prohibition on fishing in the month of their prohibition to do so. violations with different people, this does not create a deterrent effect for the perpetrators of the offense. Bengkalis, is a district in Riau Province, Indonesia. Its territory covers the eastern part of the island of Sumatra and the archipelago, with an area of 7,793.93 km2. Geographically, Bengkalis waters, located in the waters of the Malacca Strait which is a separation between two countries, Indonesia and Malaysia. These waters have fish resources that have the potential to be managed and developed as a beneficial economic growth for both countriesThis research is a type of research that is empirical or sociological legal research. Sociological legal research is research that is carried out directly in the location or in the field to obtain data to provide a complete and clear picture of the problem under study. This research is more specific to legal effectiveness. When talking about the power of law, it means talking about the power of the law in regulating and / or compelling to obey the law. This research focuses on the Criminalization Policy Against the Capturing of Terubuk Fish in the Bengkalis Regency Regional Regulation based on the Decree of the Minister of Marine Affairs and Fisheries Number KEP59 / MEN / 2011 concerning the Determination of the Limited Protection Status of Terubuk Fish, associated with criminal law policy theory and law enforcement theory.The results of this research are expected in the future in a ministerial decree to impose sanctions on the perpetrators and explain in detail what kind of protection matters should be protected. Then there should be an activity that conducts discussions with the local government by discussing that the act is a criminal act and attaching in the regulation what things are called criminalization.Keywords: Criminalization-Terubuk Fishing Policy